(untitled) (Jurnal ForestrIndo, 2025)
The level of damage to pine trees due to tapping is based on the parameters of the number of taps, width of taps, height of taps and depth of taps. The altitude at which pine trees grow can affect the recovery of pine tapping fields because weather conditions, air temperature and sunlight intensity at each altitude are different. This study aims to determine the condition of pine trees due to tapping, measure the percentage of pine tree tapping field recovery and analyze the effect of altitude on tapping field recovery. The results showed that the average tapping damage at each altitude did not meet the pine resin tapping procedures that had been implemented by Perhutani except for the average tapping height. The height of the place affects the recovery of the tapping field. The highest average percentage of tapping field recovery was found at an altitude of <400 meters above sea level (masl) with a value of 50.40%/tapping and the lowest average percentage of tapping field recovery was found at an altitude of >1,000 masl with a value of 36.05%/tapping.